Evaluating the Accuracy of Imputation Methods in a Five-Way Admixed Population - Schurz, Haiko; Müller, Stephanie J.; van Helden, Paul David; Tromp, Gerard; Hoal, Eileen G.; Kinnear, Craig J.; Möller, Marlo (Frontiers in Genetics, 2019)
Genotype imputation is a powerful tool for increasing statistical power in an association analysis. Meta analysis of multiple study datasets also requires a substantial overlap of SNPs for a successful association analysis, which can be achieved by imputation. Quality of imputed datasets is largely dependent on the software used, as well as the reference populations chosen. The accuracy of imputation of available reference populations has not been tested for the five way admixed South African Coloured (SAC) population. In this study, imputation results obtained using three freely accessible methods were evaluated for accuracy and quality. We show that the African Genome Resource is the best reference panel for imputation of missing genotypes in samples from the SAC population, implemented via the freely accessible Sanger Imputation Server.